2022
DOI: 10.3389/fmed.2022.1023879
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of participation restriction among older adults at risk of falls and relationship with intrinsic capacity: A latent cluster analysis

Abstract: IntroductionThe concept of participation restriction was first described by the World Health Organization in 2001 as a component of The International Classification of Functioning, Disability and Health Framework. Both falls and fear of falling (FOF) are associated with social isolation, depression, anxiety, poor quality of life and cognitive impairment resulting in participation restriction. Life-space mobility (LSM) is an important indicator for participation restriction which depends on multiple inter-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Liu et al demonstrated that impaired vitality, locomotion, and psychology domains predicted the incidence of future falls within two years and that cognitive decline was associated with activities of daily living dependence in the future ( 21 ). Another study suggested that older adults with falls or those at risk of falls had at least three domains of IC decline ( 47 ). Thus, older inpatients with low IC composite scores and their domains constitute a high-risk group for falls in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al demonstrated that impaired vitality, locomotion, and psychology domains predicted the incidence of future falls within two years and that cognitive decline was associated with activities of daily living dependence in the future ( 21 ). Another study suggested that older adults with falls or those at risk of falls had at least three domains of IC decline ( 47 ). Thus, older inpatients with low IC composite scores and their domains constitute a high-risk group for falls in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size varied from 100 to 37,993, with 67.9% comprising studies with fewer than 1,000 participants. About eight studies only recruited individuals with health conditions, such as hypertension, acute coronary syndrome, a history of falls within the past 12 months, or limitations in activities [27][28][29][30][31][32][33][34] (Detailed characteristics were summarized in Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Depression and FOF are the reaction of elderly psychological problems,The prevalence of FOF in elderly stroke patients with depressed mood was 3.014 times higher compared with other patients, the results are consistent with a study in South Korea, 20 depression may cause cognitive impairment, suicide, quality of life and other adverse consequences, these negative performance in turn can induce even aggravate FOF. 21 A healthy mental state is an important guarantee for the body to maintain normal emotions and maintain cognitive and physical activities. Therefore, it is necessary to implement targeted intervention for stroke patients with FOF in various aspects such as physiological, psychological and social and external environment, so as to reduce the health damage of FOF to the elderly.…”
Section: Depressionmentioning
confidence: 99%